2022
DOI: 10.1080/2162402x.2022.2096363
|View full text |Cite
|
Sign up to set email alerts
|

Trial watch: Dendritic cell (DC)-based immunotherapy for cancer

Abstract: Dendritic cell (DC)-based vaccination for cancer treatment has seen considerable development over recent decades. However, this field is currently in a state of flux toward niche-applications, owing to recent paradigm-shifts in immuno-oncology mobilized by T cell-targeting immunotherapies. DC vaccines are typically generated using autologous (patient-derived) DCs exposed to tumor-associated or -specific antigens (TAAs or TSAs), in the presence of immunostimulatory molecules to induce DC maturation, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 288 publications
0
51
0
Order By: Relevance
“…To date, more than 400 clinical trials of DC vaccines have been registered on in different cancers (accessed on 15 August 2022). Results of completed studies highlight that DC vaccines are relatively safe and result in positive patient outcomes, although in only a minority of patients [ 30 , 31 , 32 , 33 ]. Consequently, in 2010, the FDA approved the first DC vaccine (Sipuleucel-T) against metastatic prostate cancer [ 30 , 34 ].…”
Section: Immunotherapies In Ocmentioning
confidence: 99%
“…To date, more than 400 clinical trials of DC vaccines have been registered on in different cancers (accessed on 15 August 2022). Results of completed studies highlight that DC vaccines are relatively safe and result in positive patient outcomes, although in only a minority of patients [ 30 , 31 , 32 , 33 ]. Consequently, in 2010, the FDA approved the first DC vaccine (Sipuleucel-T) against metastatic prostate cancer [ 30 , 34 ].…”
Section: Immunotherapies In Ocmentioning
confidence: 99%
“…The disappointment from the early “DC era” is presumably due to the fact that many studies were not designed in combination with other immunotherapeutic interventions and patients were enrolled at late stages of the disease, often associated with advanced tumor microenvironment and the disease-elicited immune system defects [ 143 , 144 , 145 ]. However, DC-based immunotherapy still goes on through efforts to find new ways for their improvement [ 146 ]. Due to advances in genomics, many recent DC-based approaches focus on targeting neoantigens that have become considered powerful targets for cancer immunotherapy [ 147 , 148 , 149 ], including DC-based vaccines [ 150 ].…”
Section: Dcs In Immunotherapy Of Solid Tumorsmentioning
confidence: 99%
“…Three decades ago, DCs were thought to be highly promising immune cells for cancer therapy, namely, for ACT-based immunotherapy. Despite many disappointments in clinical trials, the use of these cells still showed a notable therapeutic efficacy, and their role in cancer immunotherapy is indeed still ongoing [ 146 , 154 , 155 ]. As research into immunotherapy accelerated after the immune checkpoint inhibitor had entered the field, the efficacy of DC-based immunotherapy was found to be largely restricted by the settings (immunotype) of the patient’s tumor immune microenvironment [ 153 , 156 ].…”
Section: Mc/dc Interplay As the Cellular Immune Checkpoint For Cancer...mentioning
confidence: 99%
See 1 more Smart Citation
“…In case of infections, such target cells predominantly consist of cells against which pathogenic microbes show specific tropism (e.g., epithelial, or immune cells) [ 7 ], or cells that die during host level-responses against the infection (e.g., neutrophils, macrophages, or T cells) [ 8 ]. In case of cancer, such target cells predominantly consist of cancer cells unable to cope with genetic instability or TME-associated stressors (e.g., hypoxia, acidosis, or nutrient-deprivation), followed by immune cells that die due to TME-associated stressors (e.g., neutrophils, dendritic cells) or cancer-driven direct induction of dysfunction or exhaustion (e.g., CD8 + T cells) [ 6 , 9 , 10 ]. Such cell death induced due to the progression of infection or a tumour, largely supports rather than suppress, the severity of disease and patient mortality [ 11 ].…”
mentioning
confidence: 99%